Surface Effects on Water Storage under Dryland Summer Fallow: A Lysimeter Study - Wuest, S. (2020)
Small changes in short‐ and long‐term soil water storage can affect crop productivity in semiarid climates. To optimize tillage and residue management on silt loam soils, we compared evaporation from a range of soil surface conditions in a climate with dry summers. Sixty low‐cost, low‐maintenance lysimeters were constructed from 26‐L buckets and installed in‐ground for five summers. Three summer fallow soil management options were mimicked by packing soil uniformly to the surface, putting a loose layer of fine soil on top of the packed base, or placing a mixture of clods and fine soil on top of the base. Different amounts of wheat residue on the soil surface were also tested. With three replications, the lysimeters were capable of discriminating 0.10‐mm evaporation differences between treatments at p < 0.05. Evaporation differences were small, typically only 5 mm, at the end of each summer fallow dry season. Wheat residue on the soil surface and different soil mulch treatments had little influence on evaporation during long dry periods, but surface residue had a substantial effect on soil water storage immediately after rainfall, especially as evaporative demand decreased in early autumn. The results indicate that high levels of surface residue might be more important than tillage or no‐till in the proportion of early autumn rain being stored vs. evaporated.